2011
DOI: 10.1007/s00264-010-1193-3
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fibula resection in the treatment of bone tumours

Abstract: Background and objectives We present a large study of patients with proximal fibula resection. Moreover we describe a new classification system for tumour resection of the proximal fibula independent of the tumour differentiation. Methods In 57 patients the functional and clinical outcomes were evaluated. The follow-up ranged between six months and 22.2 years (median 7.2 years). The indication for surgery was benign tumours in ten cases and malignant tumours in 47 cases. In 13 of 45 patients, where a resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
0
37
1
Order By: Relevance
“…The main therapeutic challenges, in addition to eradication of the lesion, are to avoid local recurrence, prevent damage to the growth plate, maintain fibular length, avoid progressive valgus deformity of the ankle and preserve stability of the ankle and the knee [4][5][6]. The close relation of the common peroneal nerve, the anterior tibial artery and the lateral collateral ligament to the proximal fibula are major concerns in the surgical management of proximal fibular tumors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main therapeutic challenges, in addition to eradication of the lesion, are to avoid local recurrence, prevent damage to the growth plate, maintain fibular length, avoid progressive valgus deformity of the ankle and preserve stability of the ankle and the knee [4][5][6]. The close relation of the common peroneal nerve, the anterior tibial artery and the lateral collateral ligament to the proximal fibula are major concerns in the surgical management of proximal fibular tumors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The MSTS scores of surgically treated benign and malignant proximal fibular tumors are available in the literature. Dieckmann et al [8] reported the mean MSTS scores as 90 to 97% for 57 patients with 46 malignant tumors who had undergone fibular resection for benign or malign tumors between 1987 and 2009. Inatani et al [9] reported 12 patients with benign or malignant tumors who underwent surgery between 1992 and 2011 and indicated the mean MSTS score as 96% (range, 70% and 100%) for those in whom peroneal nerve could not be resected and as 65% (range, 60% and 70%) for those in whom the nerve was resected.…”
Section: Discussionmentioning
confidence: 99%
“…An updated review of the literature regarding tumors in the proximal fibula is provided in Table II. [1][2][3][6][7][8][9]13,14] Malawer type 1 and type 2 resection is an effective surgical treatment method for tumors diagnosed early, not reaching large sizes, and with no tibial metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining at least two distal perforators, the LHBFM can also be used as 180° turnover flap for coverage of wounds around the knee joint [ 51 , 56 ]. The loss of function after separation of LHBFM is sufficiently remedied by the other ischio-crural muscles provided that they are not damaged and there is also no preexistent lateral instability in knee joint; hence, the possible postoperative loss of function and lateral knee laxity would be of relevance for athletes [ 57 - 60 ].…”
Section: Discussionmentioning
confidence: 99%